(3eTcd GdbQBfs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO bGSe Hf CUHY (B: (3bQC YdjfG GHh eMeO bJjHI bGd (B: (3GdMeO ddg GdPi fgL dfG SHd GdQTGO s
(3BNQgG (B:s
(3jfJgi CKfGA (B" (3HGH GdeJTGHg (B" (3Hbhdg aEf CYdG GdRfOjf PcQh GdCSad CfKi (B" (3hgh ef TQM HjJ CejI Hf CHj GdUdJ (B: (3hGdCQV fhcgG GdEdg WQhbI ddeGA MJi cd hfO eSaQ s
(3bWYI CNQi Ydi Qb ZRGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJaSjQ hYdhe GdbQBfs